Impedance control of a dual-arm robot. - Jassemi-Zargani, Rahim. (University of Ottawa (Canada), 1998)
Intensive research efforts are currently directed toward special robotic applications. One of the largest international projects with a focus on this research is the Space Station Freedom. Canada's contribution to this project is a Mobile Servicing System (MSS). This system will be used for assembly and maintenance of the space station. The MSS will consist of a long single arm with a dual-arm robot attached to its end. They require a hierarchical controller to coordinate the arms while executing such tasks as trajectory generation, arm-arm collision avoidance, arm-obstacle collision avoidance, and the manipulation of solid and flexible body payloads. This thesis presents the research work for building a functional hardware and software model of a test-bed dual-arm robot with flexible object handling capabilities using impedance control. It addresses issues such as input-output linearization, perturbation observer, sensor fusion, and provides the experimental results of a dual-arm manipulator using the proposed techniques. To date, no work exists which shows that the application of a dual-arm robot handling flexible payloads in space applications is possible.
Keywords: Engineering, Aerospace.